The Cultural Effect of Popular Korean Drama: Squid Game - Namiratusshofa Siregar; Alemina Br. Perangin Angin; Umar Mono (Institut Agama Islam Negeri Palopo, 2021)
AbstractNowadays, the phenomenon of squid game is exploding at an alarming rate. It does not take long for the audience to spread the drama virally, as it is so true to life. People of all ages from all over the world are extremely enthusiastic about the outcome of the drama, which is referred to as euphoria. The descriptive qualitative method was used in this study, and the author discovered that the three most famous trends inspired by the drama are red and green light, dalgona candy, and costume play. Children are more likely to not consume in order for the rating to be 18+, but the trends can't be denied at all, even when it comes to children. It also has an impact on their mental and behavioral health.